Concrete admixture with sulfate corrosion resistance and rust inhibition functions and preparation method thereof

By using admixtures composed of fly ash, barium carbonate, barium hydroxide, mineral powder, modified hydrotalcite, nanosilicon dioxide and calcium nitrite in concrete, the reduction of concrete strength in high concentration sulfate environment is solved Problem, effective sulfate corrosion resistance and rust resistance protection for concrete and steel bars is achieved.

CN119430717APending Publication Date: 2025-02-14GANSU ZHONGSEN NEW MATERIAL CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411631209.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In high concentration sulfate environments, the strength of concrete will be greatly reduced, resulting in the safety of engineering structures being threatened, especially in the bitter and salt water environments in the western region, concrete and steel structures are susceptible to sulfate corrosion and corrosion.

Method used

A concrete admixture, including fly ash, barium carbonate, barium hydroxide, ore powder, modified hydrotalcite, nanosilicon dioxide and calcium nitrite, is prepared by stirring evenly to produce sulfate corrosion resistance and rust resistance. Functional product.

Benefits of technology

This admixture can effectively inhibit the entry of sulfate into concrete pores, prevent the formation of insoluble inorganic salt crystals, improve the compressive strength and durability of concrete, and prevent corrosion of steel bars in a high-salt environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a concrete admixture with sulfate corrosion resistance and rust resistance functions. The concrete admixture is prepared from the following raw materials in parts by weight: 50-65 parts of fly ash, 8-12 parts of barium carbonate, 8-12 parts of barium hydroxide, 8-12 parts of mineral powder, 5-8 parts of modified hydrotalcite or hydrotalcite, 1-3 parts of nano silicon dioxide and 1-3 parts of calcium nitrite. Nano silicon dioxide is adopted as a compact component, the porosity of the material is reduced, the compactness of concrete is improved, sulfate in the environment is inhibited from being transmitted into the concrete, meanwhile, hydrotalcite is modified by polymaleic acid serving as a scale inhibition component, and the scale inhibition effect is improved through the dual effects of high adsorbability and slow release of the scale inhibition component of hydrotalcite. The preparation method has the advantages that generation of ettringite and gypsum in a sulfate radical environment is inhibited, calcium nitrite is added as a corrosion-inhibiting component, a protective film is formed on the surface of a reinforcing steel bar, the corrosion phenomenon of the reinforcing steel bar in a concrete structure is inhibited, and finally, the concrete admixture with sulfate corrosion resistance and corrosion-inhibiting functions is formed through compounding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and relates to a concrete admixture with sulfate corrosion resistance and rust prevention functions and a preparation method thereof. Background Art

[0002] Concrete is the main material in engineering construction and is widely used in the fields of construction, water conservancy and hydropower, transportation, etc. Under normal circumstances, the service life of concrete is usually long. However, if concrete is placed in a high-concentration sulfate environment for a long time, the strength of the concrete will be greatly reduced, seriously affecting the safety of the engineering structure. The groundwater in western regions (such as Gansu, Qinghai, etc.) is mostly brackish water, with extremely high sulfate and chloride content in the environment. In addition, the temperature difference between day and night is large, and the climate is dry, which makes it easy for concrete to be in a harsh environment with high concentrations of sulfate and chloride and alternating dry and wet cycles for a long time. Concrete and steel structures are facing erosion and damage from high-salt environments. Therefore, concrete foundation construction in western regions is at potential risk of being damaged by sulfate erosion, and it is crucial to improve the durability of concrete projects in different environments.

[0003] The principle of sulfate attack on concrete is that sulfate in the external environment enters the pores of concrete, reacts chemically with the hydration products in the concrete and gradually forms insoluble inorganic salt crystals. Therefore, how to inhibit sulfate in the environment from entering the pores of concrete and inhibit the formation of insoluble inorganic salts is the key to inhibiting sulfate attack. Summary of the invention

[0004] In view of the above technical problems, the purpose of the present invention is to provide a concrete admixture with sulfate corrosion resistance and rust prevention function and a preparation method thereof, which is used to inhibit concrete corrosion and corrosion of steel bars in high sulfate and chloride environments.

[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: A concrete admixture with sulfate corrosion resistance and rust prevention functions comprises the following raw materials in parts by weight: 50-65 parts of fly ash, 8-12 parts of barium carbonate, 8-12 parts of barium hydroxide, 8-12 parts of mineral powder, 5-8 parts of modified hydrotalcite, 1-3 parts of nano silicon dioxide with a particle size of about 30-40 nm, and 1-3 parts of calcium nitrite. The above raw materials are added into a reaction kettle, stirred at a speed of 300 rpm for 20 minutes until uniform, and the final product is obtained.

[0006] Among them: the modified hydrotalcite uses natural mineral hydrotalcite as raw material, calcining the hydrotalcite at 450-550 ℃ for 3-5 hours to remove water molecules between the hydrotalcite layers, and then dispersing the calcined hydrotalcite in a polymaleic acid aqueous solution with a concentration of 0.125%, stirring at room temperature for 1-3 hours, standing for 70-75 hours, and then drying at 55-65 ℃ for 20-25 hours to allow polymaleic acid anions and water molecules to be intercalated into the hydrotalcite interlayer, on the one hand, to restore the layered structure of the hydrotalcite, and at the same time, to slowly release the polymaleic acid anions into the environmental system to play a role in scale inhibition. At the same time, based on the strong adsorption properties of hydrotalcite to sulfate, the formation of sulfate erosion products in the environment, ettringite and gypsum, is inhibited.

[0007] When the concrete admixture of the present invention is used, the dosage is 5-10% of the concrete cementitious material to ensure the durability of the test piece.

[0008] The invention has simple production process and convenient operation, and the final product has both sulfate erosion resistance and corrosion resistance.

[0009] The raw materials used in the present invention, such as fly ash, barium carbonate, barium hydroxide, mineral powder, nano silicon dioxide, calcium nitrite and hydrotalcite, are all commercially available commodities.

[0010] The following tests were conducted on the relevant technical performances of the concrete admixture with sulfate corrosion resistance and rust prevention functions of the present invention: 1. Test methods The rust inhibition and corrosion resistance of the rust inhibitor component calcium nitrite on steel bars was tested according to the weight loss method. First, steel bars with a diameter of 6 mm and a length of 6 cm were ultrasonically cleaned with acetone and deionized water, respectively, and then naturally dried. The initial weight (g) of the steel bars was weighed, and then the steel bars were placed in mixed solutions containing different rust inhibitor components and 1.5% NaCl and 3.5% Na2SO4 for 7 days and 28 days. After the expiration, the soaked steel bars were cleaned and weighed, and the mass difference before and after immersion (△m) was calculated. The weight loss rate of steel bars at two ages in different solutions was calculated. In addition, the weight loss rate of steel bars in deionized water without adding rust inhibitor, aqueous solution containing 1.5% NaCl and 3.5% Na2SO4, and solution containing 1% water reducer was tested as a comparative experiment. The results are shown in Table 1.

[0011] In the preparation of concrete specimens, the concrete design strength is C30, and the mix ratio of concrete specimens is shown in Table 2. Seven admixture formulas with different proportions were designed (as shown in Table 3), and the admixture dosage was 5-10% of the concrete cementitious material. 100 mm*100 mm*100 mm cubic concrete specimens with different admixtures were made, and the compressive strength (MPa) of the specimens was tested after curing in a standard curing box for 7 days and 28 days. Figure 1 .

[0012] According to GB / T 50082-2009, test the material's resistance to sulfate corrosion. According to the method and steps for testing compressive strength, 100 mm*100 mm*100 mm cubic concrete specimens with different admixtures were made. After curing the specimens for 28 days, they were placed in a dry-wet cycle test device and a comparative experiment was conducted. After 90 days of dry-wet cycles, the compressive strength of the concrete specimens that had undergone dry-wet cycles of sulfate solution was tested. The compressive strength corrosion resistance coefficient KS of the material was calculated based on the compressive strength of the experimental specimens and the compressive strength of the comparison group. See Figure 2 .

[0013] 2. Test results As shown in Table 1, the weight loss rates of steel bars placed in deionized water, mixed solution of NaCl and Na2SO4 and 1% water reducer for 7 days were 0.7224‰, 0.8837‰ and 0.6543‰ respectively. The results show that the steel bars have serious corrosion in the mixed solution of NaCl and Na2SO4, and even in deionized water, the steel bars still have relatively serious corrosion. In the solution containing different amounts of calcium nitrite, the steel bars did not have obvious corrosion, and the weight loss rate was close to 0. As the age was extended to 28 days, the corrosion of the steel bars in deionized water, NaCl and Na2SO4 solution and 1% water reducer became more serious, and the weight loss rate of the steel bars increased to 2.3504‰, 2.8618‰ and 2.1882‰, which were 3.25 times, 3.24 times and 3.34 times of the age of 7 days, respectively. The weight loss rate of steel bars in the systems containing 1%, 2%, and 5% rust inhibitors still did not increase significantly, indicating that calcium nitrite can still inhibit the corrosion of steel bars over time. The results show that 1-5% calcium nitrite can effectively inhibit the corrosion of steel bars. Considering the economic cost, the amount of calcium nitrite is usually 1%.

[0014] Depend on Figure 1It can be seen that the 7d compressive strength of concrete specimens made with admixtures containing nano-silica dense components (ZS-1, ZS-2, ZS-3) reached 31.3, 36.7, and 32.3 MPa, respectively, and the 28d compressive strength was 35.4, 40.67, and 36.5 MPa, which were all higher than those of blank concrete specimens without admixtures. The 7d compressive strength and 28d compressive strength of concrete specimens made of admixtures containing only modified hydrotalcite (ZS-4, ZS-5) are lower than those containing unmodified hydrotalcite (ZS-6). The results show that using modified hydrotalcite alone can easily reduce the compressive strength of concrete specimens. When an appropriate amount of modified hydrotalcite and nano-silica are used in combination, the compressive strength of the concrete specimens is higher than the compressive strength of the concrete specimen without dense components and unmodified hydrotalcite (ZS-6), indicating that dense components and modified hydrotalcite can improve the compressive strength of concrete specimens through synergistic effects.

[0015] Figure 2 The compressive strength and corrosion resistance coefficient of concrete specimens with different admixtures after 90 dry-wet cycles in sodium sulfate aqueous solution are compared. Figure 2 It can be seen that the compressive strength and corrosion resistance coefficients of concrete specimens made with admixtures containing nano-silica dense components (ZS-1, ZS-2, and ZS-3) are 1.07, 0.97, and 1.16, which are higher than those of concrete specimens made with admixtures that do not contain dense components, indicating that dense component nano-silica can effectively improve the compressive strength and corrosion resistance coefficient of concrete. The reason may be that nano-silica, as a dense component, reduces the porosity of concrete and improves the density of concrete. Without considering the influence of dense components, the compressive strength corrosion resistance coefficient of the admixture (ZS-5) containing 8% modified hydrotalcite is 0.99 after 90 dry-wet cycles in sodium sulfate aqueous solution, which is higher than that of the concrete specimen (ZS-6) without dense components and unmodified hydrotalcite. However, the compressive strength corrosion resistance coefficient of the admixture (ZS-4) with a modified hydrotalcite dosage of 6% has decreased. The results show that only an appropriate amount of modified hydrotalcite can improve the compressive strength corrosion resistance coefficient of concrete. The reason may be that the polymaleic acid anion plays a scale inhibition role, inhibiting the formation of calcium sulfonate and gypsum in the sulfate environment, and may play a more important role with the increase of dry-wet cycles. At the same time, the concrete specimen (ZS-3) containing unmodified hydrotalcite and dense component admixture has good compressive strength and corrosion resistance coefficient. The reason is that hydrotalcite has good adsorption capacity for sulfate ions in the system, which can inhibit the formation of sulfate corrosion products such as ettringite and improve the density of concrete.

[0016] The invention uses 30-40nm nano silicon dioxide as a dense component to reduce the porosity of the material, improve the density of the concrete, and inhibit the transmission of the medium containing sulfate radicals into the interior of the concrete. The modified hydrotalcite is used as a carrier for slowly releasing the scale-inhibiting component and the strong adsorption to inhibit the generation of ettringite and gypsum in the sulfate radical environment. Calcium nitrite is added as a rust-inhibiting component to form a protective film on the surface of the steel bar to inhibit the corrosion of the steel bar in the concrete. Finally, a concrete admixture with the functions of resisting sulfate erosion and inhibiting rust is formed by compounding. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Compressive strength of concrete specimens with different admixtures Figure 2 Compressive strength and corrosion resistance coefficient of concrete specimens with different admixtures after 90 dry-wet cycles. DETAILED DESCRIPTION

[0018] The concrete admixture with sulfate corrosion resistance and rust prevention function of the present invention is further described below through specific examples.

[0019] Example 1 The modified hydrotalcite is made of natural mineral hydrotalcite as raw material. 10g of hydrotalcite is heated to 500℃ at a heating rate of 2℃ / min and calcined for 4 hours to remove water molecules between hydrotalcite layers. The calcined hydrotalcite is then dispersed in a 0.125% polymaleic acid aqueous solution, stirred for 2 hours, allowed to stand for 72 hours, and then dried at 60℃ for 24 hours to obtain the modified hydrotalcite.

[0020] The concrete admixture was prepared according to the proportion of 6 parts of modified hydrotalcite, 2 parts of nano-silicon dioxide (dense component), 1 part of calcium nitrite, 61 parts of fly ash, 10 parts of barium carbonate, 10 parts of barium hydroxide, and 10 parts of mineral powder. The above raw materials were added to the reactor and stirred at a speed of 300 rpm for 20 minutes until uniform, and the concrete admixture was obtained, which was marked as ZS-1. A 100 mm*100 mm*100 mm cubic concrete specimen was made with a 5% concrete admixture dosage. The compressive strength of the concrete specimen was 31.3 MPa after curing for 7 days, and the compressive strength of the concrete specimen was 35.4 MPa after curing for 28 days. The compressive strength corrosion resistance coefficient of 90 dry-wet cycles was 1.07.

[0021] Example 2 The preparation of modified hydrotalcite is the same as in Example 1; the concrete admixture is prepared according to the ratio of 8 parts of modified hydrotalcite, 2 parts of nano-silicon dioxide (dense component), 1 part of calcium nitrite, 59 parts of fly ash, 10 parts of barium carbonate, 10 parts of barium hydroxide, and 10 parts of mineral powder. The other steps are the same as in Example 1 to prepare a concrete admixture, marked as ZS-2. The compressive strength of the concrete specimen after curing for 7 days is 36.7 MPa, and the compressive strength of the concrete specimen after curing for 28 days is 40.67 MPa. The compressive strength corrosion resistance coefficient of 90 dry-wet cycles is 0.97.

[0022] Example 3 The concrete admixture was prepared according to the ratio of 8 parts of hydrotalcite, 2 parts of dense components, 1 part of calcium nitrite, 59 parts of fly ash, 10 parts of barium carbonate, 10 parts of barium hydroxide, and 10 parts of mineral powder. The other steps were the same as those in Example 1. The concrete admixture was prepared and marked as ZS-3. The compressive strength of the concrete specimen after curing for 7 days was 32.3 MPa, and the compressive strength of the concrete specimen after curing for 28 days was 36.5 MPa. The compressive strength corrosion resistance coefficient of 90 dry-wet cycles was 1.16.

Claims

1. A concrete admixture having sulfate corrosion resistance and rust resistance function, characterized in that: The raw materials include the following parts by weight: 50-65 parts of fly ash, 8-12 parts of barium carbonate, 8-12 parts of barium hydroxide, 8-12 parts of mineral powder, 5-8 parts of modified hydrotalcite or hydrotalcite, 1-3 parts of nano silicon dioxide, and 1-3 parts of calcium nitrite; The modified hydrotalcite uses natural mineral hydrotalcite as a raw material, calcines the hydrotalcite at 450-550°C for 3-5 hours to remove water molecules between hydrotalcite layers, disperses the calcined hydrotalcite in a polymaleic acid aqueous solution, stirs at room temperature for 1-3 hours, stands for 70-75 hours, and then dries at 55-65°C for 20-25 hours to obtain the modified hydrotalcite.

2. The concrete admixture having sulfate corrosion resistance and rust resistance function according to claim 1, characterized in that: The mass concentration of the polymaleic acid aqueous solution is 0.125%.

3. The concrete admixture having sulfate corrosion resistance and rust resistance function according to claim 1, characterized in that: The particle size of nano-silica is 30-40 nm.

4. The method for preparing the concrete admixture having sulfate corrosion resistance and rust prevention function according to claim 1, characterized in that: According to the proportion, 50-65 parts of fly ash, 8-12 parts of barium carbonate, 8-12 parts of barium hydroxide, 8-12 parts of mineral powder, 5-8 parts of modified hydrotalcite or hydrotalcite, 1-3 parts of nano-silicon dioxide and 1-3 parts of calcium nitrite are weighed and added into a reaction kettle, and stirred evenly to obtain the final product.

5. The method for preparing the concrete admixture having sulfate corrosion resistance and rust prevention function according to claim 4, characterized in that: The stirring was carried out at a speed of 300 rpm for 20 min until the mixture was homogeneous.

Citation Information

Cited By

  • Lithium slag-based salt corrosion resistant concrete pole and preparation method thereof

    CN121270212A

  • Preparation method of carbonate corrosion resistant lining concrete

    CN122187430A

  • A method of preparing a carbonate corrosion resistant lining concrete

    CN122187430B

  • Concrete admixture against endogenous type of sulphate attack, method of preparation and quantification method

    CN122627711A